Methods of Teaching Foreign Languages Using Social Networks - Dilafruz Javliyeva Rustam qizi (Journal of Higher Education and Academic Advancement, 2024)
This article analyzes the multifunctionality of the language of mass communication. It is the language of different social and cultural strata. Speech heard on the radio or on the screen often approaches speech that is simple, used in everyday life. As a result, the language of communication becomes richer and more diverse.